The Relationship Between Personal Hygiene and The Prevalence of Tinea Unguium Infection Among Farmers in Jember District - Mufida, Diana Chusna; Himma, Alyatul; Agustina, Dini; Armiyanti, Yunita; Sofiana, Kristianningrum Dian (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2024)
Tinea unguium is an infection of the nail caused by dermatophyte fungi. Nails infected with the fungus will be discolored, thick, and brittle. Personal hygiene is one of the risk factors that can affect tinea unguium. This study aimed to determine the relationship of personal hygiene to the prevalence of tinea unguium infection in farmers in the Jember Regency. The benefits of research can be used as a source of information about the importance of maintaining personal hygiene to avoid fungal infections that cause tinea unguium. This study used an analytic observational method with a cross-sectional approach. This research was conducted from August to December 2023 in 10 districts of Jember Regency. The population in this study were all farmers in Jember Regency. The sample in this study was calculated by the Slovin formula and obtained from as many as 100 farmers who met the inclusion and exclusion criteria. Sampling using mixed methods sampling. The statistical analysis used is Cramer's V test α = 0.05. The results of this study show a significant relationship between personal hygiene and the prevalence of tinea unguium in farmers in Jember Regency with a p-value of 0.004 (0,004<0,05).